2022
DOI: 10.3390/jcm11030639
|View full text |Cite
|
Sign up to set email alerts
|

Neural Substrates of Transcutaneous Spinal Cord Stimulation: Neuromodulation across Multiple Segments of the Spinal Cord

Abstract: Transcutaneous spinal cord stimulation (tSCS) has the potential to promote improved sensorimotor rehabilitation by modulating the circuitry of the spinal cord non-invasively. Little is currently known about how cervical or lumbar tSCS influences the excitability of spinal and corticospinal networks, or whether the synergistic effects of multi-segmental tSCS occur between remote segments of the spinal cord. The aim of this review is to describe the emergence and development of tSCS as a novel method to modulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 106 publications
1
31
0
Order By: Relevance
“…These implications should be carefully considered when other electrode configurations (e.g. the anode electrode is placed on the iliac crests [1][2][3][4]) are used while continuous stimulation is delivered, since the excitability of the sensory and motor fibers could be different [16,64]. For instance, de Freitas et al [16] suggested that nerve fiber activation thresholds are higher when the anode is placed at the iliac crests compared to the anterior neck anode placement.…”
Section: Implications For Therapeutic Application Of Cervical Tscsmentioning
confidence: 99%
See 1 more Smart Citation
“…These implications should be carefully considered when other electrode configurations (e.g. the anode electrode is placed on the iliac crests [1][2][3][4]) are used while continuous stimulation is delivered, since the excitability of the sensory and motor fibers could be different [16,64]. For instance, de Freitas et al [16] suggested that nerve fiber activation thresholds are higher when the anode is placed at the iliac crests compared to the anterior neck anode placement.…”
Section: Implications For Therapeutic Application Of Cervical Tscsmentioning
confidence: 99%
“…Cervical transcutaneous spinal cord stimulation (tSCS) has recently emerged as a non-invasive rehabilitation technology for recovery of upper-limb motor function after spinal cord injury [1][2][3][4]. Neuromodulation of cervical spinal neural circuitries may occur when cervical tSCS is combined with supraspinal descending drive, promoting neuroplasticity across the damaged spinal regions [1,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, transcutaneous spinal cord stimulation (TSCS), a non-invasive method of spinal stimulation, has emerged as a successful neuromodulation technique for enhancing motor function post-SCI ( Megía García et al, 2020 ; Taylor et al, 2021 ; Rehman et al, 2023 ). TSCS is generally divided into two different categories: direct current (DC-TSCS) and alternating current (AC-TSCS) ( Taylor et al, 2021 ; Barss et al, 2022 ; Rahman et al, 2022 ). In DC-TSCS (also called transspinal direct current stimulation: tsDCS), a constant electrical current, usually in the range of 1–2.5 mA, flows in a constant direction and the polarity of stimulation is defined based on the polarity of the electrode placed on the spine (cathodal or anodal) ( Grecco et al, 2015 ; Rahman et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous spinal cord stimulation (TSS) has emerged as a complementary therapy to restore motor function in people with spinal cord injury (SCI; Megía‐García et al, 2020 ; Rahman et al, 2022 ; Shackleton et al, 2022 ). By stimulating afferent nerve fibers in the dorsal roots, TSS is thought to reflexively increase motoneurone excitability, which improves the ability of descending motor drive to recruit additional motoneurones below the level of the SCI (Barss et al, 2022 ; Mayr et al, 2016 ; Taccola et al, 2018 ). Despite its growing popularity, some fundamental aspects of TSS methodology have yet to be explored systematically.…”
Section: Introductionmentioning
confidence: 99%